The Effect of Individual Coping and Family Support in Reducing the Anxiety Level of Hemodialysis Patients at Imelda General Hospital Indonesia - Naibaho , Eka Nugraha V.; Loka, Tya Pita; Ritonga, Yuni Shanti (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Chronic renal failure (CRF) is a condition of kidney function that decreases gradually due to kidney damage. Patients undergoing hemodialysis therapy will face problems arising from malfunctioning of the kidneys. Coping mechanism is one way to adapt to stress. Family support is an attitude, action, acceptance of the family and ready to provide help and assistance to one of the families who is sick or needs help and causes a sense of love and affection. The purpose of the study was to determine the effect of individual coping and family support in reducing the anxiety level of hemodialysis patients at Imelda General Hospital Indonesia in 2023. This type of research is quantitative research. The study was conducted at Imelda Indonesia Hospital Medan in August 2023. The study population was 104 hemodialysis patients, the study sample was 52 people with purposive sampling. Bivariate Analysis with Chi Square test. The results of the study The age of the majority of hemodialysis respondents aged 46-55 years (Early Elderly) as many as 26 people (50.0%), the majority sex is male as many as 28 people (53.8%), Long time undergoing hemodialysis the majority of 1-3 years as many as 30 people (57.7%), Adaptive coping (62-100) as many as 49 people (94.2%), Good family support (36-48) as many as 50 people (96.2%), Mild anxiety levels (20-39) as many as 42 respondents (80.8%), Adaptive coping individuals (62-100) had an effect with mild anxiety levels (20-39) as many as 40 people with P Value values of 0.035<0.05. Good family support (36-48) had an effect with mild anxiety levels (20-39) as many as 42 people with P Value 0.013<0.05.